Prototype for fit investigations - Alsardia, Talal; Lovas, László; Ficzere, Péter (Design of Machines and Structures, 2021)
Nowadays, additive manufacturing is a powerful tool and promising technology both for manufacturing and educational purposes. This work aims to present a case study of using 3 dimensional (3D) printing technology for fit investigations. It describes the creation of a physical model (prototype) by using the Fused Deposition Modeling (FDM) method. The prototype of two plates was made to perform an inspection how the prototype fits with other components.